Implementasi Mengenai Perjanjian Kredit Dengan Jaminan Bpkb Di PT. International Finance : (Studi PT. FIF Group Cabang Lombok Barat) - I Kadek Tisna; Aris Munandar; Wiwiek Wahyuningsih (Fakultas Hukum Universitas Mataram, 2023)
Purpose of this research is to know the implementation of credit agreement with proof of vehicle ownership (Bukti Pemilikan Kendaraan Bermotor-BPKB) as guarantee and also to know the obstacles in its implementation at PT. International Finance. Method of this study was normative empirical legal research, which applied statute, conceptual and sociological approaches. Implementation of credit agreement with BPKB is started with the debtor comes to the FIF Office and bring some required documents and until the signature of credit agreement phase. Obstacles in the implementation of credit agreement is the breach of contract, consumer data, vehicle tax and guarantee execution. The method to overcome the problem is “Collection Management or Account Receivable (AR) Management”.